"You've Gotta Set a Precedent": Māori and Pacific voices on student success in higher education. Issue 2 (June 2014) - Mayeda, David Tokiharu; Keil, Moeata; Dutton, Hilary Dansey; Ofamo'Oni, I.-Futa-Helu
A substantial body of literature has examined the challenges that indigenous students face in higher education. Across Aotearoa New Zealand, the indigenous Māori population is under-represented at the university level, as are ethnically diverse Pacific students who trace their ancestries to neighbouring Pacific nations. This study relies on focus group interviews with high-achieving Māori and Pacific students (N = 90) from a large New Zealand university. Using kaupapa Māori (theory and methodology grounded in a Māori world view) and Pacific research principles, the study identifies the social factors contributing to indigenous students' educational success. Three broad themes emerged from discussions: family and university role modelling and support; indigenous teaching and learning practices; and resilient abilities to cope with everyday colonialism and racism. A positive indigenous ethnic identity ties these themes together, ultimately serving as the steady factor driving Māori and Pacific students' achievement motivation.